Associations of circulating polyunsaturated fatty acids with coronary artery calcium score in hospitalized patients with suspected coronary artery disease. (14th October 2021) - Karaji, I; Aakre, K M; Omland, T; Lonnebakken, M T; Vikenes, K; Pedersen, E R
Abstract: Background: Inadequate intake of polyunsaturated fatty acids (PUFAs) is recognized as a modifiable risk factor for atherosclerotic cardiovascular disease (CVD) (1, 2). The n-6 PUFA linoleic acid (LA) constitutes the predominant portion of total dietary PUFAs (3). However, whereas cardiometabolic effects of PUFAs belonging to the n-3 series have been studied for decades, less attention has been payed to potential health effects from n-6 PUFAs (4). Further, there has been concern regarding possible proinflammatory properties of several n-6 PUFA related metabolites. Purpose: We explored correlations of serum total PUFAs, LA and the n-3 PUFA docosahexaenoic acid (DHA) with the inflammation marker GlycA. Further, we evaluated associations of total PUFAs, LA and DHA with the extension of atherosclerosis, as determined by the Agatston coronary artery calcium (CAC) score (5). Methods: The study includes 250 patients who were hospitalized due to acute chest pain and referred to coronary CT angiography (CCTA) during in hospital stay. Exclusion criteria included diagnosis of acute myocardial infarction and/or revascularization within 24 hours after admittance. Serum levels of total PUFAs, LA, DHA and GlycA were analyzed by NMR technology in samples that had been frozen and stored at −80°C. After logarithmic transformation, relations of total PUFA, LA, and DHA with GlycA were evaluated by Pearson correlation analyses. The associations with CAC score were visualized in generalized additive regression plots and further evaluated in linear regression models including age, gender, body mass index, diabetes, hypertension and smoking status as independent covariables. Results: Mean (SD) age was 57.6 (12.0) years, and 91 (36.4%) of the patients were women. Median (25th-75th percentiles) serum levels (in mmol/L) were for total PUFA 6.36 (5.76–7.06), LA 5.00 (4.51–5.55), DHA 0.36 (0.31–0.43) and GlycA 1.04 (0.94–1.13). Interestingly, GlycA was strongly, positively correlated with total PUFA (r=0.54). LA (r=0.53) and DHA (r=0.27), all P<0.001. In contrast, total PUFA and LA were inversely associated with CAC score both providing standardized betas of −0.17, P=0.03 after multivariable adjustments. No significant associations were found between CAC score and DHA or GlycA (P≥0.22). Further, the addition of GlycA to the multivariable model did not materially affect the relationship between CAC score and total PUFA or LA, which remained statistically significant (P=0.04). Conclusion: In patients undergoing CCTA due to acute chest pain, serum levels of total PUFA and LA were strongly positively correlated with the pro-inflammatory marker GlycA. Still, total PUFA and LA were both inversely associated with the CAC score and the associations remained statistically significant after adjustments for CVD risk factors and GlycA levels. Future studies should further address the diverse effects of n-6 PUFAs on inflammatory pathways, atherogenesis and coronary calcification. FUNDunding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Western Norway Regional Health Authority